Determinants of Factors Affecting Mortality of Patients Covid-19 in Pregnant Women in Province West Nusa Tenggara - Rohani Rohani; Sudarmi Sudarmi; Irianto Irianto (Indonesian Journal of Global Health Research, 2021)
In Indonesia, maternal mortality and neonatal mortality are big challenges and need attention in the Covid-19 disaster situation. This study aims to determine the determinants of factors that affect the mortality of Covid-19 patients in pregnant women in Province West Nusa Tenggara. The design of this study was a cross-sectional with purposive sampling technique, namely all pregnant, maternity and, postpartum women diagnosed with Covid-19 with PCR swab (+) who were treated in hospitals throughout the province of NTB during the period March to December 2020. Data collected through the register with a total sample of 163 people. The variables of this study were age, obstetric status, cluster, treatment status and, history of co-morbidities. Data were analyzed using bivariate analysis using Chi-Square and multivariate with Logistic Regression. The results of the study were that most of the mothers were aged 20-23 years (66.3%), obstetric status during the puerperium (58.3%), without cluster (97.5%), cured status (98.2%) and, without comorbidities. (97.5%). Maternal age and obstetric status did not show a significant relationship with their respective scores (p=0.819 and p=0.808), while clusters and comorbidities showed a significant relationship (p=0.000). Clusters and comorbidities are the most dominant in influencing mortality of Covid-19 patients in pregnant women and contributing 86.7%, the rest is influenced by other factors.